IMPLEMENTASI PEMBIASAAN BERDOA DALAM MEMBENTUK KARAKTER RELIGIUS ANAK USIA 5–6 TAHUN DI TK ISLAM TERPADU RAUDHATUL JANNAH CILEGON - Zamelia Maulida; Fadlullah; Fahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of prayer habituation, the strategies employed by teachers, and the challenges encountered in fostering the religious character of children aged 5–6 years at TK Islam Terpadu Raudhatul Jannah Cilegon. A descriptive qualitative approach was used, involving the principal, teachers, and children in Group B as participants. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model consisting of data reduction, data display, and conclusion drawing. The findings show that prayer habituation has become an integral part of daily school activities, carried out before and after learning, during mealtimes, and in other routine activities. Teachers applied strategies such as role modeling, repetition, motivation, songs and simple movements, and positive reinforcement. These practices positively influenced children's religious character development, reflected in their increasing habit of praying, using Islamic expressions, polite behavior, gratitude, and active participation in religious activities. Challenges included differences in children's ability to memorize prayers, understand prayer etiquette, and maintain concentration. Continuous collaboration between school and parents is essential for optimal development of children's religious character.